Simulations of Water and Thermal Dynamics for Soil Surfaces With Residue Mulch and Surface Runoff. Issue 11 (10th November 2021) - Wang, Zhuangji; Thapa, Resham; Timlin, Dennis; Li, Sanai; Sun, Wenguang; Beegum, Sahila; Fleisher, David; Mirsky, Steven; Cabrera, Miguel; Sauer, Thomas; Reddy, Vangimalla R.; Horton, Robert; et al.
Abstract: Water and thermal dynamics at soil surfaces are influenced by multiple ambient factors, for example, weather, soil, residue mulch, and surface runoff. A surface water and temperature model should address those ambient factors, and their interactions and derivatives. In this study, we developed a process‐based simulation model for surface water and heat transfer with two main ambient factors, residue mulch and surface runoff. Surface water content and temperature are simulated with a modified Philip and de Vries (1957) model, including precipitation interception and radiation attenuation in residue mulch. Surface runoff is modeled with the Saint‐Venant equation. Residue decomposition, as a derivative, is computed via a modified CERES‐N model. Interactions between surface runoff and residue mulch, and dynamic decreases in residue mulch thickness due to decomposition are also included. The model was modularized and deployed with a "layered module architecture" in MAIZSIM, such that the main ambient factors, interactions, and derivatives can be activated or deactivated based on scenarios or user settings. Illustrative examples include non‐decomposable residue mulch, surface runoff and mulch decomposition scenarios. Results demonstrate that residue mulch can conserve soil water and reduce temporal variations of surface temperature. Surface runoff and its effects on water infiltration and surface temperature, and nitrogen mineralization during decomposition are also illustrated. The simulated surface temperature, water content, and mulch decomposition results are similar to literature results from field experiments. This study demonstrates the model workability in simulating surface water and temperature dynamics, and the feasibility of synthesizing multiple factors via a modularized model architecture. Plain Language Summary: Knowledge of the impacts on residue mulch and surface runoff on surface soil is important for agricultural field management. We developed a new method to simulate the moisture and thermal regimes on soil surface with residue mulch and/or surface runoff using a computer program. The computer program can also present the surface runoff and residue decomposition. The program can estimate the nitrogen and carbon (organic matter) exchanges between residue mulch and surface soil. This information will be useful to scientists, agricultural managers and consultants. Key Points: A numerical model is developed to simulate soil surface water and temperature with residue mulch and runoff Water and thermal simulations are adaptive to mulch decomposition and shrinkage Mulch residue decomposition and N mineralization rate are estimated by the model